International marketing and export management - Albaum, Gerald; Duerr, Edwin (Addison-Wesley, 2011)
International Marketing and Export Management 7th edition offers an accessible and authoritative perspective on international marketing with a strong export management orientation, comprehensively describing the evolving competitive landscape as created by technological advances and international trade patterns. The seventh edition retains its clear and informed coverage of the opportunities for companies of all sizes and in all industries in the export of goods, services, intellectual property and business models